La doppiezza di un letterato (Bisanzio e l'Occidente, 2019)
This paper deals with the behaviour of Michael Psellos, perhaps the greatest intellectual of the XI cen-tury in the Byzantine empire, in the very troubled epoch between the dead of Basil II and the coming in power of the Comnenians. Psellos did absolutely have no scruples about provoking the political and physical ruin of the illfated emperor Romanus IV after the battle of Mantzikert. Notwithtstanding he showed his rhetoric virtuosity in a consolatory and canting letter addressed to the blinded emperor. Far more objective was Michael Attaliates, Psellos’ contemporary. He saw the wiknesses of emperor Ro-manos, but he condemned the duplicity of Psellos himself.